Facile synthesis for well‐defined A2B miktoarm star copolymer of poly(3‐hexylthiophene) and poly(methyl methacrylate) by the combination of anionic polymerization and click reaction. Issue 10 (14th February 2013) - Park, Jicheol; Moon, Hong Chul; Kim, Jin Kon
Abstract We have introduced a facile synthetic route for well‐defined A2B miktoarm star copolymer composed of regioregular poly(3‐hexylthiophene) and poly(methyl methacrylate) ((P3HT)2PMMA) by the combination of anionic polymerization and click reaction. First, we synthesized PMMA terminated with 1, 3, 5‐tris(bromomethyl)benzene (PMMA‐(Br)2) by anionic polymerization, and two bromines attached to the end of the PMMA chains were replaced by azides (PMMA‐(N3)2). Also, monoethynyl‐capped P3HT was synthesized by Grignard metathesis polymerization and post‐end functionalization. Then, copper(I)‐catalyzed Huisgen 1, 3‐dipolar cycloaddition click reaction between monoethynyl‐capped P3HT and PMMA‐(N3)2 was performed to synthesize (P3HT)2PMMA. We used a slightly excess amount of monoethynyl‐capped P3HT so that all of the azide groups at the end of the PMMA chains completely reacted with monoethynyl‐capped P3HT. After complete removal of unreacted monoethynyl‐capped P3HT by column chromatography, pure (P3HT)2PMMA with narrow molecular weight distribution (the polydispersity of 1.18) was obtained. The weight fraction of P3HT and the total molecular weight of (P3HT)2PMMA are 0.48 and 16, 000, respectively. To investigate the effect of the chain architecture on optical property and thin‐film morphology, we synthesized two linear P3HT‐b‐PMMAs (P3HT‐b‐PMMA‐L and P3HT‐b‐PMMA‐H) with similar weight fraction of P3HT block (0.48 for P3HT‐b‐PMMA‐L and 0.45 for P3HT‐b‐PMMA‐H) but two different total molecular weights (7900 for P3HT‐b‐PMMA‐L and 15, 300 for P3HT‐b‐PMMA‐H). UV–visible (UV–vis) absorption spectrum and the fibril width of (P3HT)2PMMA thin film were similar to those of P3HT‐b‐PMMA‐L thin film. However, UV–vis spectrum for P3HT‐b‐PMMA‐H thin film was red‐shifted and the fibril width of P3HT‐b‐PMMA‐H was much larger than that of (P3HT)2PMMA. This indicates that the π–π interaction between P3HT arms in (P3HT)2PMMA is strong enough to arrange two P3HT backbone chains in (P3HT)2PMMA to stack one by one along the nanofibril axis. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013